Baş Boyun Kanserleri - Küçüktağ, Zülküf; Mutlu, Murad; Kaya, Altan; Aytaç, İsmail; Güzel, Berkay; Kumbul, Yusuf Çağdaş; Kaplan, Büşra; Özlügedik, Samet; Cebeci, Süleyman; İriz, Ayşe; Kılıç, Caner; Koci, Mert Burak; et al. (2023)
-